2019
DOI: 10.1136/postgradmedj-2019-136683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a gender-affirming healthcare curriculum for second-year medical students

Abstract: BackgroundTransgender medicine is an emergent subfield with clearly identified educational gaps.AimsThis manuscript evaluates a gender-affirming healthcare curriculum for second-year medical (M2) students.MethodsStudents received a survey assessing Gender Identity Competency in terms of skills, knowledge and attitudes regarding transgender and gender non-conforming (TGNC) issues. The authors administered the survey before and after the delivery of the curriculum. The curriculum included five online modules, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Of these, 398 full texts from the original search and 147 full texts from the updated search (final total of 545) were reviewed for inclusion. A final set of 51 full-text articles in the primary search [ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 ], as well as 28 full-text articles in the updated search [ 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 ] were selected for qual...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 398 full texts from the original search and 147 full texts from the updated search (final total of 545) were reviewed for inclusion. A final set of 51 full-text articles in the primary search [ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 ], as well as 28 full-text articles in the updated search [ 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 ] were selected for qual...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies described assessment of more than one health profession [ 21 25 26 28 31 34 42 51 54 68 77 98 ]. Cultural competency (56; 70.9%) [ 21 22 23 24 25 28 30 32 34 36 37 38 39 42 43 44 45 46 47 50 51 52 54 55 56 57 58 61 62 65 66 68 71 72 73 75 77 78 79 80 81 82 83 84 85 87 88 89 90 91 93 94 95 96 97 98 ] was the most common aspect of global health subject area, and most studies reported data resulting from standard live didactic course structures (58; 73.4%) [ 20 22 23 24 25 26 28 29 30 31 32 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations